COMBAT EXPOSURE AND LIFE SATISFACTION IN OLDER VETERANS: THE MODERATING ROLE OF THE QUALITY OF MATERNAL RELATIONSHIP. (11th November 2018) - Carr, D; Sachs-Ericsson, N; Taylor, M
Abstract: Nearly half of men over 50 in the US are veterans. Despite this common experience, we are only beginning to understand how military experiences during early life influence later life wellbeing. Recent research suggests that combat experience in particular has important implications for later life health, with research showing associations with enhanced resilience to physical health on the one hand, and increased risk of mental health consequences on the other hand relative to veterans not exposed to combat. One of the factors that may explain these differential effects may relate to how other early life experiences moderate the impact of combat experiences among men. In this study, we examine how early life maternal relationships interact with exposure to combat on life satisfaction in later life among male veterans. Our sample is drawn from the HRS 2013 Veteran Mail Survey and data drawn from the larger HRS study, including 307 veterans exposed to combat and 823 veterans not exposed to combat. Results show that among those men with the lowest maternal relationship scores, combat exposed veterans had a lower life satisfaction score (marginally significant) compared to those without combat exposure (a predicted value of 4.1 vs. 4.7; p=0.08). However, among those who reported the highest maternal relationships early in life, combat exposure was associated with higher life satisfaction compared to those not exposed to combat (a predicted value of 5.4 vs. 5.1; p<0.05). These findings suggest the effect of combat on later life wellbeing is dependent on other early life factors.